(untitled) (Ciudades, 2018)
The Local Society of Land and Housing of Valladolid (VIVA) has been the sponsoring entity of the “Estudio de remodelación de los barrios de Pajarillos y Rondilla”, written by the University Institute for Urban Research of the University of valadolid (IUU) collaborating with Inzamac-Tecopy. Covadonga Magdalena is an achitect of VIVA and, as such, has been the technical representative of the city hall on the discussions for the elaboration and passing of this work awarded the "European Prize Gubbio 2003". Her participation on the debate over the contents of the Study with the representatives of other urban agents implicated on it has made her deserve, in the opinion of the IUU, a space in Ciudades where she can explain the institutional policy and her personal impressions about this experience.